2015
DOI: 10.1101/014407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Crossmodal integration improves sensory detection thresholds in the ferret

Abstract: During the last two decades ferrets (Mustela putorius) have been established as a highly efficient animal model in different fields in neuroscience. Here we asked whether ferrets integrate sensory information according to the same principles established for other species. Since only few methods and protocols are available for behaving ferrets we developed a head-free, body-restrained approach allowing a standardized stimulation position and the utilization of the ferret's natural response behavior. We establis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 68 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…When stimulus intensity is high, the need to perform multisensory integration to detect the stimulus is low, because the unisensory stimulus is easily perceivable; however, multisensory integration is still required to differentiate uni-from multisensory stimuli. During low-intensity stimulation, detection of sensory stimuli is more difficult, and integrating information from different modalities can help this process (Gleiss and Kayser, 2012;Hollensteiner et al, 2015). In line with this, we previously showed that the behavioral gain during multisensory detection is highest when the unisensory stimulus constituents are presented around their perceptual thresholds, but is largely absent when the stimulus intensities are higher (Meijer et al, 2017).…”
Section: Cross-modal Modulation Of Neural Responses To Highand Low-contrast Stimulimentioning
confidence: 63%
“…When stimulus intensity is high, the need to perform multisensory integration to detect the stimulus is low, because the unisensory stimulus is easily perceivable; however, multisensory integration is still required to differentiate uni-from multisensory stimuli. During low-intensity stimulation, detection of sensory stimuli is more difficult, and integrating information from different modalities can help this process (Gleiss and Kayser, 2012;Hollensteiner et al, 2015). In line with this, we previously showed that the behavioral gain during multisensory detection is highest when the unisensory stimulus constituents are presented around their perceptual thresholds, but is largely absent when the stimulus intensities are higher (Meijer et al, 2017).…”
Section: Cross-modal Modulation Of Neural Responses To Highand Low-contrast Stimulimentioning
confidence: 63%
“…Fortunately, it turned out that ferrets can be readily trained to carry out sensory tasks. This species is increasingly being used to study aspects of visual (Garipis & Hoffmann, ; Von Melchner, Pallas & Sur, ; Zhou, Yu, Sellers & Fröhlich, ) and multisensory behaviour (Hammond‐Kenny, Bajo, King & Nodal, ; Hollensteiner, Pieper, Engler, König & Engel, ), and has been employed extensively in a range of auditory detection, discrimination and localization tasks (reviewed by Fritz, Elhilali, David & Shamma, ; Nodal & King, ).…”
Section: Experience‐dependent Plasticity In Developing Sensory Systemsmentioning
confidence: 99%
“…Ferrets have been used extensively in physiological and anatomical studies of multisensory processing (e.g. King & Hutchings, 1987;King et al, 1988;King & Schnupp, 2000;Bizley et al, 2007;Bizley & King, 2008;Stitt et al, 2015), but only to a limited degree so far in behavioural experiments (Isaiah et al, 2014;Hollensteiner et al, 2015), despite the ease with which they can be trained to carry out localization and other sensory tasks. We have previously characterized sound localization behaviour in this species by measuring their head-orienting response following stimulus presentation and the subsequent locomotor response as the animals approach the perceived location of the sound source to receive a water reward (Nodal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%